Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Cooperative Learning Tipe Talking Stick pada Pembelajaran IPAS di Kelas IV UPT SDN 23 Tandai Solok Selatan - Esa, Aprilian Kurnia; Iraqi, Hana Shilfia; Erita, Yeni; Arwin, Arwin (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to describe how the improvement of student learning outcomes in IPAS learning using the Cooperative Learning model of Talking Stick type in the fourth-grade class of UPT SDN 23 Tandai, Solok Selatan District. This type of research is Classroom Action Research (CAR) using two types of approaches, namely qualitative and quantitative approaches. The research was conducted in two cycles, with the research procedure consisting of planning, implementation, observation, and reflection. Data collection techniques included observation analysis, tests, and non-tests. The subjects of this study were the researcher teacher as an observer, the fourth-grade teacher as a practitioner, and 20 students from the fourth grade of UPT SDN 23 Tandai. The results showed that in cycle I the average score of the teaching module was 93.9% (SB), which increased to 100% (SB) in cycle II. The results of the implementation of the learning aspect of the teacher in cycle I obtained an average of 93% (SB), which increased in cycle II to 98% (SB). The results of the implementation of the learning aspect of the students in cycle I obtained an average of 89.5% (SB), which increased in cycle II to 98% (SB). The learning outcomes of the students in cycle I obtained an average of 75.8 (C), which increased in cycle II to 87.8 (B). Thus, it can be concluded that the Cooperative Learning model of the Talking Stick type can improve students' learning outcomes in the IPAS learning in grade IV UPT SDN 23 Tandai, South Solok Regency.